2013
DOI: 10.1089/neu.2012.2715
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Hemorrhagic Shock on Cerebral Blood Flow, Brain Tissue Oxygen Tension, and Spreading Depolarization following Penetrating Ballistic-Like Brain Injury

Abstract: Traumatic brain injury (TBI) often occurs in conjunction with additional trauma, resulting in secondary complications, such as hypotension as a result of blood loss. This study investigated the combined effects of penetrating ballistic-like brain injury (PBBI) and hemorrhagic shock (HS) on physiological parameters, including acute changes in regional cerebral blood flow (rCBF), brain tissue oxygen tension (P(bt)O₂), and cortical spreading depolarizations (CSDs). All recordings were initiated before injury (PBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
5
17
2
Order By: Relevance
“…22 Combined hypoxemia and hemorrhagic shock in animal models of TBI + HS have been associated with transient intracerebral reductions in brain glucose, pyruvate, and prolonged elevations of lactate. 23,24 Energy-related neurochemical dysregulation in TBI + HS is likely a major factor contributing to worse neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Combined hypoxemia and hemorrhagic shock in animal models of TBI + HS have been associated with transient intracerebral reductions in brain glucose, pyruvate, and prolonged elevations of lactate. 23,24 Energy-related neurochemical dysregulation in TBI + HS is likely a major factor contributing to worse neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas brain injury has been shown to cause altered vascular compensation in response to HS, 31 questions remain about the relationship between coagulopathy and the size of brain lesions. 15,22,30,32,33 Ratio-guided resuscitation with fresh frozen plasma (FFP) may have beneficial effects for patients with TBI + HS, 15 including fewer inflammatory complications. 5,6,9 In experimental large animal studies, early administration of FFP reduced the size of brain lesions, decreased cerebral edema, and substantially attenuated the degree of neurological impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, rodents subject to penetrating ballistic-like brain injury (PBBI) display a 70% reduction in regional cerebral blood flow (CBF) ipsilateral to the injury as compared to baseline. PBBI also decreases brain tissue oxygenation tension and causes spreading cortical depolarizations shortly after injury [5]. CBF reductions are more pronounced in older compared to younger rodents, as seen with fluid percussion injury (FPI) TBI [6].…”
Section: Early Phasementioning
confidence: 99%
“…It is very sensitive to ischemia and hypoxia. When the cerebral blood flow (CBF) is less than 12-20 ml/ (100 g/min), it will lead to insufficient blood supply to the brain [2], causing microcirculation perfusion, functional disorders of cell membrane Na-K pump, intracellular anaerobic glycolysis, generation of cytotoxic edema, ischemia, bloodbrain barrier damages, and further aggravation of the brain damage. Study has showed microcirculation perfusion abnormalities that appeared before the cytotoxic edema and vasogenic edema [3].…”
Section: Introductionmentioning
confidence: 99%